2024
DOI: 10.3389/fimmu.2024.1381227
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress: bridging inflammation and obesity-associated adipose tissue

Kaile Ma,
Yanjiao Zhang,
Jingyi Zhao
et al.

Abstract: Obesity presents a significant global health challenge, increasing the susceptibility to chronic conditions such as diabetes, cardiovascular disease, and hypertension. Within the context of obesity, lipid metabolism, adipose tissue formation, and inflammation are intricately linked to endoplasmic reticulum stress (ERS). ERS modulates metabolism, insulin signaling, inflammation, as well as cell proliferation and death through the unfolded protein response (UPR) pathway. Serving as a crucial nexus, ERS bridges t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 130 publications
(138 reference statements)
0
1
0
Order By: Relevance
“… 140 Excess metabolites in the ER compartment can disrupt the interactions of 78 kDa GRP78 with inositol‐requiring enzyme 1, protein kinase R‐like ER kinase, and activating transcription factor 6 (ATF6), leading to ER stress and metabolic inflammation. 141 Previously, celastrol was shown to reduce ER stress; however, the exact molecular mechanisms and target proteins involved have not been determined. 142 In 2022, Rong's group 143 showed that GRP78 was the major celastrol‐bound protein in RAW264.7 murine macrophages.…”
Section: The Effects and Functional Targets Of Natural Products In Th...mentioning
confidence: 99%
“… 140 Excess metabolites in the ER compartment can disrupt the interactions of 78 kDa GRP78 with inositol‐requiring enzyme 1, protein kinase R‐like ER kinase, and activating transcription factor 6 (ATF6), leading to ER stress and metabolic inflammation. 141 Previously, celastrol was shown to reduce ER stress; however, the exact molecular mechanisms and target proteins involved have not been determined. 142 In 2022, Rong's group 143 showed that GRP78 was the major celastrol‐bound protein in RAW264.7 murine macrophages.…”
Section: The Effects and Functional Targets Of Natural Products In Th...mentioning
confidence: 99%